Refractory composite sheet
By adopting multi-layered textile parts and polymer-coated composite sheets, the problem of difficult to provide efficient fireproof and lightweight cargo container wall materials in the prior art is solved, and improved fire resistance and weight reduction effects are achieved.
Patent Information
- Application Number
- CN202380056725.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-09
- Filing Date
- 2023-06-07
- Publication Date
- 2025-03-18
AI Technical Summary
The prior art is difficult to provide refractory composite sheets for cargo container walls and it is desirable to improve fire protection while reducing weight.
Using composite sheets including textile parts and polymer coatings, the textile parts consist of woven fabrics of continuous filament yarns, nonwoven fabrics and another woven fabric of continuous filament yarns, and attached by bonding, stitching or fiber entanglement, the coating provides UV and environmental resistance.
Provides improved fire protection while reducing weight, effectively blocking flame penetration in fire situations and maintaining performance after a wash-drying cycle.
Smart Images

Figure CN119654233A_ABST
Abstract
Description
Background Art 1. Technical Field
[0001] The disclosed embodiments generally relate to a composite sheet material having fire resistant properties. The sheet material can be used as curtain wall for fire resistant cargo containers, particularly containers used in aircraft. 2. Background Art
[0003] The amount of cargo carried in both passenger and cargo aircraft has been increasing for many years. At the same time, there is a growing concern about the risk of fire in cargo containers due to the increase in the amount of power sources in the cargo, such as high-density energy storage devices or other battery types. Five recent developments in fire-resistant composite sheets for cargo container walls are described below.
[0004] U.S. Patent No. 9,296,555 to Kawka and Chang relates to a non-rigid composite sheet comprising, in sequence, (i) a first component having an areal density of 88 to 678 gsm, the first component comprising a first filament yarn fabric having a tenacity of at least 11 grams per decitex (g / dtex) and a first polymer layer that is UV-impermeable and weatherproof, (ii) a second component having an areal density of 30 to 237 gsm, the second component comprising a flame retardant substrate and an inorganic fire resistant layer, and (iii) a third component having an areal density of 88 to 678 gsm, the third component comprising a second filament yarn fabric having a tenacity of at least 11 grams per decitex and a second polymer layer that is impact-resistant and scratch-resistant, the second fabric of the third component being adjacent to the fire resistant layer of the second component.
[0005] U.S. Patent No. 9,302,845 to Kawka and Chang discloses a non-rigid composite sheet comprising, in sequence, a first component having an areal density of 102 to 678 gsm, the first component comprising a first filament yarn fabric having a tenacity of at least 11 g / dtex and a first polymer layer that is UV-impermeable and weatherproof; a second component having an areal density of 10 to 170 gsm, the second component comprising a flame-retardant inorganic fire-resistant layer adjacent to at least one protective polymer layer; and a third component having an areal density of 102 to 678 gsm, the third component comprising a second filament yarn fabric having a tenacity of at least 11 g / dtex and a second polymer layer that is impact-resistant and scratch-resistant, the second fabric of the third component being adjacent to the fire-resistant layer of the second component.
[0006] U.S. Patent No. 10,457,013 to Kawka and Perez teaches a non-rigid composite sheet comprising, in sequence, (i) a first component having an area weight of 88 to 678 gsm, the first component comprising a first filament yarn fabric having a tenacity of at least 11 g / dtex and a first polymer layer that is UV-impermeable and weather-resistant, (ii) a second component having an area weight of 120 to 430 gsm, the second component comprising a flame-retardant paper, and (iii) a third component having an area weight of 88 to 678 gsm, the third component comprising a second filament yarn fabric having a tenacity of at least 11 g / dtex and a second polymer layer that is impact-resistant and scratch-resistant, the second fabric of the third component being adjacent to the paper of the second component.
[0007] U.S. Patent No. 9,993,989 issued to Kawka describes a non-rigid composite sheet comprising, in sequence, (i) a first component comprising a first continuous filament yarn fabric having a tenacity of at least 11 grams per dtex and a first polymer layer, (ii) a second component comprising at least one second continuous filament glass yarn fabric, the second fabric being adjacent to the first fabric of the first component, and (iii) a third component comprising a second polymer layer.
[0008] U.S. Patent No. 10,300,677 to Kawka relates to a non-rigid composite sheet comprising, in sequence, (i) a first component comprising at least one first continuous filament yarn fabric having a tenacity of at least 11 g / dtex and a first polymer layer, (ii) a second component comprising at least one second continuous filament glass yarn fabric, the at least one second fabric being adjacent to the at least one first fabric of the first component, and (iii) a third component comprising a second polymer layer.
[0009] However, there remains a need and desire for additional fire resistant composite sheets for cargo container walls that will provide improved fire protection. Further weight reduction is also desired. Summary of the invention
[0010] In one aspect, the present disclosure provides a composite sheet 11a or 11b, comprising a textile component 12a or 12b having a first surface 13a or 13b or a second surface 14a or 14b, and a first polymer coating 15 on the first surface 13a or 13b of the textile component 12a or 12b. The textile component 12a or 12b further comprises
[0011] a fabric structure 16 of a woven fabric of at least one continuous filament yarn, the fabric having an area weight of from about 70 to about 508 gsm,
[0012] a nonwoven fabric structure 17 comprising a blend of discontinuous oxidized polyacrylonitrile fibers and silica fibers, wherein the oxidized polyacrylonitrile fibers are present in an amount of about 30 to about 70 weight percent of the combined weight of the oxidized polyacrylonitrile fibers and the silica fibers, and
[0013] A fabric structure 18 of at least one woven fabric of continuous filament yarns, the fabric having an area weight of about 70 to about 508 gsm. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 is an exploded end view of a composite sheet 11a according to an exemplary embodiment.
[0015] Figure 2 is an exploded end view of a composite sheet 11b according to an exemplary embodiment.
[0016] Figure 3 is an end view of textile component 12a illustrating stitching through three textile structures 16 - 18 of textile component 12a according to an exemplary embodiment.
[0017] Figure 4 is an end view of textile component 12a illustrating filament entanglement between three textile structures 16 - 18 of textile component 12a according to an exemplary embodiment. DETAILED DESCRIPTION
[0018] In the following detailed description, reference is made to the accompanying drawings, which form a part of the detailed description and illustrate exemplary embodiments of the present invention. These embodiments will be described in sufficient detail to enable those of ordinary skill in the art to make and use them. It should also be understood that structural, logical or procedural changes may be made to the exemplary embodiments disclosed herein without departing from the spirit or scope of the present invention.
[0019] Figure 1 An exemplary exploded end view of one embodiment of a composite refractory sheet 11a is generally shown at 10a. The composite sheet 11a includes a textile component 12a having a first surface 13a and a second surface 14a and a polymer coating 15 located on the first surface 13a of the textile component 12a. An optional second polymer coating 19 may be located on the second surface 14a of the textile component 12a.
[0020] Figure 2An exemplary exploded end view of another embodiment of a composite refractory sheet 11b is generally shown at 10b. The composite sheet 11b includes a textile component 12b having a first surface 13b and a second surface 14b and a polymer coating 15 located on the first surface 13b of the textile component 12b. An optional second polymer coating 19 may be located on the second surface 14b of the textile component 12b.
[0021] Textile parts
[0022] Textile component 12a or 12b includes three different textile structures.
[0023] The fabric structure 16 comprises at least one woven fabric of continuous filament yarns.
[0024] Fabric structure 17 is a nonwoven fabric of a blend of discontinuous fibers including oxidized polyacrylonitrile fibers and silica fibers. In some embodiments, the oxidized polyacrylonitrile fibers are present in an amount of about 30 to about 70 weight percent of the combined weight of the oxidized polyacrylonitrile fibers and the silica fibers, and in other embodiments, in an amount of about 40 to about 60 weight percent of the combined weight of the oxidized polyacrylonitrile fibers and the silica fibers. In some embodiments, the nonwoven fabric has an area weight of about 100 to about 170 gsm, in other embodiments about 100 to about 240 gsm, and in other embodiments about 100 to about 305 gsm. Preferably, fabric structure 17 includes only one nonwoven fabric, but more than one nonwoven fabric may be incorporated into fabric structure 17.
[0025] Fabric structure 18 comprises at least one woven fabric of continuous filament yarns.
[0026] exist Figure 1 In the embodiment, fabric structure 17 is located between fabric structure 16 and fabric structure 18. Fabric structure 17 of textile component 11a may be attached to fabric structure 16 or fabric structure 18 or both of fabric structure 16 and fabric structure 18 by attachment means. In other embodiments, such as Figure 2 As shown, fabric structure 18 is located between fabric structure 16 and fabric structure 17. Fabric structure 18 of textile component 12b may be attached to fabric structure 16 or fabric structure 17 or to both fabric structure 16 and fabric structure 17 by attachment means.
[0027] Suitable attachment means for attaching two or all three fabric structures 16, 17, and 18 together include, but are not limited to, bonding, sewing, or fiber entanglement.
[0028] Bonding can be achieved by placing an adhesive (preferably an adhesive film) between one or more of the fabric structures 16, 17 and 18 and curing the adhesive, or by impregnating one or more of the fabric structures 16, 17 and 18 with a matrix resin, placing one or more of the impregnated fabric structures in contact with another fabric structure and curing the matrix resin.
[0029] Figure 3 An example cross-sectional view of a stitching option is shown, wherein stitch 20 passes through fabric structures 16 - 18 of textile component 12a .
[0030] Figure 4 An example of a cross-sectional view of a fiber entanglement option is shown. This is commonly referred to as needle punching or needling. In this process, fine needle barbs repeatedly penetrate the textile component 12a, causing the filaments 21 to be redirected and extend in the z direction generally perpendicular to the xy plane of the textile component 12a. This intermixing of the filaments 21 between the different fabric structures 16, 17 and / or 18 improves the flame retardancy of the textile component.
[0031] In some embodiments, some combination of bonding, sewing, or fiber entanglement may be used as the attachment means.
[0032] In a preferred embodiment, all three fabric structures 16, 17 and 18 are attached to each other by attachment means.
[0033] Figure 1 and 2 The textile structures 16, 17 and 18 of textile component 12a or 12b are shown arranged in a particular order. Other arrangements are also suitable, for example, textile structure 16 may be positioned between textile structure 17 and textile structure 18.
[0034] When tested according to ASTM D1876-08 (2015) - Standard Test Method for Peel Resistance of Adhesives, the textile component 12a or 12b should preferably have a fabric-to-fabric bond strength of at least 11 kg / 10 cm when subjected to puncture, i.e., there is no delamination between the fabric structure 16 and the fabric structure 17 or between the fabric structure 16 and the fabric structure 18 or between the fabric structure 17 and the fabric structure 18 until a tensile strength of at least 11 kg / 10 cm is reached.
[0035] In some embodiments, one or more of the fabric structures 16, 17, or 18 of the textile component 12a or 12b is impregnated with a matrix resin such that the resin is present in an amount of about 5 to about 45 weight percent of the combined weight of the resin and the fibers in each of the one or more impregnated fabric structures, in other embodiments, about 7 to about 40 weight percent of the combined weight of the resin and the fibers in each of the one or more impregnated fabric structures, in other embodiments, about 7 to about 20 weight percent of the combined weight of the resin and the fibers in each of the one or more impregnated fabric structures, and in other embodiments, about 15 to about 20 weight percent of the combined weight of the resin and the fibers in each of the one or more impregnated fabric structures. The matrix resin can be a phenolic resin, a flame retardant epoxy resin, or a flame retardant polyurethane. Bio-based resins such as bio-based perfluoroalkoxy copolymers, bio-based epoxy glass polymer materials, bio-based polyetherimides, lignin bio-based phenolic resins, bio-based polycarbonates, soy-based unsaturated polyesters, bio-based benzoxazines, bio-based epoxy resins, and green polyethylene can also be used. Cure the resin following the recommended cure cycle from the supplier. A continuous belt press is an example of equipment where the curing process may be affected.
[0036] In a preferred embodiment, all three fabric structures 16, 17 and 18 are impregnated with a matrix resin. In yet another embodiment, all three fabric structures 16, 17 and 18 are attached to each other by attachment means and are impregnated with a matrix resin.
[0037] Embodiments in which at least one textile structure 16, 17 or 18 of the textile component 12a or 12b is impregnated with resin provide a composite sheet 11a or 11b that is rigid and has limited roll-up capability. Embodiments in which the textile component 12a or 12b is not impregnated with resin provide a semi-rigid (i.e., flexible and rollable) composite sheet 11a or 11b.
[0038] Woven fabrics
[0039] Suitable weave patterns for the one or more woven fabrics of fabric structure 16 and fabric structure 18 include plain weave, satin weave, basket weave, leno weave or twill weave, respectively. A suitable fabric for the one or more woven fabrics of fabric structure 16 and fabric structure 18 is a 1500 denier 29 para-aramid yarn, clean, 230 gsm, 17×17 (pick count), plain weave fabric. Alternatively, one or more woven fabrics of fabric structure 16 and fabric structure 18 can be a plain weave fabric comprising 555 dtex (500 denier) KM2+ para-aramid yarn in both the warp and fill directions at 11 ends / cm (28 ends / inch). Where there is more than one woven fabric in fabric structure 16 or fabric structure 18, the woven fabrics can be the same or different in yarn composition and / or weave pattern. In some embodiments, one or more woven fabrics of fabric structure 16 or fabric structure 18 have an area weight of about 70 to about 508 gsm (2.1 to 15 ounces per square yard), in other embodiments, about 101 to about 373 gsm (3 to 11 ounces per square yard), and in other embodiments, about 101 to about 170 gsm (3 to 5 ounces per square yard). In some other embodiments, one or more woven fabrics of fabric structure 18 have an area weight of about 170 to about 270 gsm (5 to 8 ounces per square yard).
[0040] In some embodiments, one or more woven fabrics of fabric structure 16 and / or fabric structure 18 are washed or heat cleaned after weaving. Such processes are well known in the textile industry to remove contaminants such as oils from the weaving process.
[0041] One or more woven fabrics of fabric structures 16 and 18 are made of multifilament yarns with multiple filaments. Yarn can be wound and / or twisted. For the purpose of this paper, the term "long filament" is defined as a relatively flexible, macroscopically uniform body with a high aspect ratio across its cross section perpendicular to its length. The filament cross section can be any shape but is typically circular or bean-shaped. In this article, the term "fiber" can be used interchangeably with the term "long filament", and when relating to warp and weft density, the term "single line (end)" can be used interchangeably with the term "yarn".
[0042] The filaments can have any length. Preferably, the filaments are continuous. The multifilament yarn spun to the bobbin in the package contains a plurality of continuous filaments. The multifilament yarn can be cut into staple fibers and made into a spun staple yarn suitable for use in one or more woven fabrics of fabric structure 16 and / or fabric structure 18. The staple fibers can have a length of about 1.5 to about 5 inches (about 3.8 cm to about 12.7 cm). The staple fibers can be straight (that is, non-curled) or curly with a zigzag curl along its length, wherein the curling (or repeated bending) frequency is about 3.5 to about 18 curls / inch (about 1.4 to about 7.1 curls / cm).
[0043] In some embodiments, the yarns of the one or more woven fabrics of fabric structures 16 and 18 have a yarn tenacity of at least about 11 grams per dtex and a modulus of at least about 100 grams per dtex. In some embodiments, the yarns of the one or more woven fabrics of fabric structures 16 and 18 have a linear density of about 333 to about 2222 dtex (300 to 2000 denier), in other embodiments about 555 to about 1111 dtex (500 to 1000 denier), in other embodiments about 555 dtex, and in other embodiments about 1111 dtex.
[0044] The fibers of the yarn can be polymeric, inorganic or natural, and can be made of any suitable material known in the art. In some embodiments, the fibers of the yarn can be aromatic polyamides, aromatic copolyamides, aliphatic polyamides, polyolefins, polyazoles, glass, carbon, multicomponent fibers, and combinations thereof.
[0045] When the polymer is a polyamide, aramid is preferred. As used herein, "aramid" means a polyamide polymer in which at least 85% of the amide (-CONH-) linkages are directly attached to two aromatic rings. Para-aramid polymers are aramid polymers in which the amide linkages are in a para position relative to each other. A preferred para-aramid polymer is poly(p-phenylene terephthalamide) or PPD-T. Additives can be used with aramids, and in fact it has been found that other polymeric materials up to 10 weight percent can be blended with the aramid, or copolymers can be used, which have up to 10% of other diamines replacing the diamines of the aramid or up to 10% of other diacid chlorides replacing the diacid chlorides of the aramid. Suitable aramid fibers are described in Man-Made Fibres-Science and Technology, Volume 2, in the section entitled Fibre-Forming Aromatic Polyamides, page 297, W. Black et al., Interscience Publishers, 1968. Aramid fibers and their production are also disclosed in U.S. Pat. Nos. 3,767,756; 4,172,938; 3,869,429; 3,869,430; 3,819,587; 3,673,143; 3,354,127; and 3,094,511.
[0046] Other useful para-aramids include aramid copolymers derived from combinations and / or substitutions of other aromatic diamines and other aromatic diacid chlorides, such as, for example, 2,6-naphthaloyl chloride or chloroterephthaloyl chloride or dichloroterephthaloyl chloride or 3,4'-diaminodiphenyl ether. Another preferred para-aramid includes aromatic polyamide copolymers derived from 5(6)-amino-2-(p-aminophenyl)benzimidazole (DAPBI), p-phenylenediamine (PPD) and terephthaloyl dichloride (TC1 or T, also commonly referred to as terephthaloyl chloride); for example, as in U.S. Patent Publication No. 2014 / 0357834, Russian Patent Application No. 2,045,586, and other such fibers provided in, for example, Sugak et al., Fibre Chemistry, Vol. 31, No. 1, 1999; U.S. Patent No. 4,018,735; and WO 2008 / 061668 and US 2014 / 357834-A1.
[0047] Examples of commercially available para-aramid fibers include aramid fibers from DuPont of Wilmington, Delaware. and Teijin Aramid from Arnhem, the Netherlands Examples of aramid copolymer fibers include aramid copolymer fibers from Kamenskvolokno Company, Kamensk-Shakhtinskii, Russia. and
[0048] Glass fibers may include "E" glass and "S" glass. E-glass is a commercially available low-alkali glass. A typical composition consists of: 54 wt% SiO 2 , 14 wt% Al 2 O 3 , 22 wt% CaO / MgO, 10 wt% B 2 O 3 and less than 2 wt% Na 2 O / K 2 O. Some other materials may also be present at impurity levels. S-glass is a commercially available magnesium oxide-aluminum oxide-silicate glass. This composition is harder and stronger than E-glass and is often used in polymer matrix composites. Exemplary woven fabrics of fabric structure 18 include heat-cleaned weave pattern 7781 with E-glass yarns and weave pattern 6781 with S-glass yarns.
[0049] Suitable carbon fibers are standard or intermediate modulus fibers such as those available from Toray Industries under the trade name Torayca or from Hexcel Corporation as HexTow. Typically such fibers have 3,000 or 6,000 or 12,000 or 24,000 filaments per bundle.
[0050] In some embodiments, fabric structure 16 and / or fabric structure 18 may be optionally treated with a flame retardant composition. Suitable flame retardant compositions include, but are not limited to, antimony trioxide, halogenated flame retardants (including tetrabromobisphenol A, polybrominated biphenyls, pentabromodiphenyl ether (oxide), octabromodiphenyl ether (oxide), decabromodiphenyl ether (oxide), and hexabromocyclododecane). Phosphorus-containing flame retardants are also widely used.
[0051] Polymer coating
[0052] The polymer of the first polymer coating 15 or the second polymer coating 19 may be a thermoplastic polymer, a thermosetting polymer or a silicone rubber.
[0053] Suitable polymers include polyurethane, polyethylene, polypropylene, polyethylene naphthalate, polyacrylonitrile, fluoropolymers, polyimide, polyketone, polyimide Polysulfones, polyarylene sulfides, liquid crystal polymers, polycarbonates, and ionomers such as ethylene methacrylic acid copolymers (E / MAA).
[0054] Exemplary fluoropolymers include polyvinyl fluoride Ethylene chlorotrifluoroethylene copolymer and polytetrafluoroethylene Exemplary polyketones include polyetheretherketone (PEEK) and polyetherketoneketone (PEKK).
[0055] In one embodiment, the first polymer coating 15 is a polyurethane. In another embodiment, the second polymer coating 19 is an ionomer resin (such as ethylene methacrylic acid copolymer). In yet another embodiment, the first polymer coating 15 is opaque and opaque to UV rays. By opaque and opaque to UV rays, we mean that at least 95% of the UV rays, more preferably at least 98% and most preferably 100% of the UV rays are blocked, especially those at the upper end of the UV spectrum.
[0056] In some embodiments, the first polymer coating 15 and / or the second polymer coating 19 has an area weight of about 17 to about 170 gsm (0.5 to 5 ounces per square yard), in other embodiments, about 34 to about 136 gsm (1 to 4 ounces per square yard), and in other embodiments, about 67 to about 102 gsm (2 to 3 ounces per square yard).
[0057] Preferably, the first and second polymer coatings 15 and 19 can be polyurethane, silicone rubber, polyvinyl chloride, or a blend thereof, respectively. In some embodiments, the second polymer coating 19 can be an ionomer resin based on ethylene acid copolymer (e.g. ).
[0058] First polymer coating 15 contacts first surface 13a or 13b of textile component 12a or 12b. First polymer coating 15 provides chemical and environmental (ie, weather and UV) resistance to both physical and chemical attack and liquid penetration.
[0059] By chemical and environmental / weather resistance is meant the ability of the polymer coating to withstand the effects of wind, rain, contaminants (such as acidic and / or oily residues) found in typical industrial areas, and sunlight exposure without excessive degradation. Preferably, the first polymer coating 15 has enhanced resistance to damage caused by chemical reactivity or solvent action from hydrocarbons, chemicals, ozone, bacteria, fungi and moisture, as well as skin care oils typically associated with the operation and maintenance of commercial aircraft.
[0060] UV resistant means that when exposed to ultraviolet radiation, the first polymer coating 15 maintains its appearance and physical integrity without excessively reducing its flexibility or mechanical properties (i.e., brittleness). Preferably, the polymer layer blocks at least 95% of UV rays, more preferably at least 98%, and most preferably 100% of UV rays. The UV opacity of the first polymer coating 15 can be further mitigated by including additives in the polymer material. Examples of such additives include fillers, pigments, stabilizers, and lubricants. The outer surface of the first polymer coating 15 that is not in contact with the fabric structure 16 can optionally be coated or treated with a UV blocking material.
[0061] Ultraviolet (UV) is an invisible band of radiation at the upper end of the visible spectrum. At wavelengths ranging from 10 to 400 nm, ultraviolet (UV) begins at the end of visible light and ends at the beginning of X-rays. Since the primary exposure of the composite sheet 11a or 11b to UV light is the sun, the most critical UV resistance is that to the lower frequency, longer wavelength rays.
[0062] Preferably, the first polymer coating 15 has a soft, non-plastic feel, which is ideal for products that come in contact with human skin, and maintains its toughness and flexibility over a wide temperature range, even at temperatures as low as -50°C (-60°F), over the useful life of the product.
[0063] In some embodiments, the outer surface of the first polymer coating 15 (i.e., the surface not in contact with the fabric structure 16) has a release value of no more than 263 N / m (1.5 lb. / in), more preferably no more than 438 N / m (2.5 lb. / in), when measured according to ASTM D2724-07 (2011) e1 Standard Test Methods for Bonded, Fused, and Laminated Apparel Fabrics. This facilitates cleaning, label removal, etc.
[0064] In some embodiments, the fabric structure 16 can be bonded to the first polymer coating 15 by means (such as adhesives, thermal bonding) or by fasteners. Such adhesives can be thermoplastic or thermosetting resins. Thermosetting resins include, but are not limited to, epoxy resins, epoxy novolacs, phenolic resins, polyurethanes, and polyimides. Thermoplastic resins include, but are not limited to, polyesters, polyetherketones, polyetheretherketones, polyetherketoneketones, polyethersulfones, and polyolefins. Thermoplastic resins are preferred.
[0065] Preferably, the adhesive may optionally contain up to about 40 weight percent of a flame retardant component. Suitable flame retardant components include, but are not limited to, antimony trioxide, halogenated flame retardants (including tetrabromobisphenol A, polybrominated biphenyls, pentabromodiphenyl ether (oxide), octabromodiphenyl ether (oxide), decabromodiphenyl ether (oxide), and hexabromocyclododecane). Phosphorus-containing flame retardants are also widely used.
[0066] Preferably, the adhesive blocks at least about 95% of UV rays, more preferably at least about 98%, and most preferably about 100% of UV rays.The adhesive may further contain fillers, pigments, stabilizers, and other performance enhancing additives.
[0067] Preferably, the adhesive bond between the first polymer coating 15 and the fabric structure 16 is at least about 263 N / m (1.5 lb. / in). In some embodiments, the adhesive bond between the first polymer coating 15 and the fabric structure 16 is at least about 438 N / m (2.5 lb. / in), and in other embodiments is about 876 N / m (5 lb. / in).
[0068] A second polymer coating 19, which is the innermost layer of the composite sheet 11a or 11b, contacts the second surface 14a or 14b of the textile component 12a or 12b. The second polymer coating 19 may also be colored and contain an ultraviolet (UV) blocker. Acceptable UV resistance is the ability to withstand exposure to strong direct sunlight for 10 years without compromising the basic mechanical and visual properties of the sheet. A suitable standard is ASTM G154-16 (UVA-340 lamp, 16 hours of UV at 60°C ± 2°C over a period of 240 hours, and 8 hours of condensation at 50°C ± 2°C.
[0069] In some embodiments, the fabric structure 18 may be bonded to the second polymer coating 19 ( Figure 1 ), or the nonwoven fabric structure 17 may be bonded to the second polymer coating 19 ( Figure 2 ). Suitable bonding means may be adhesive, thermal bonding, or utilizing fasteners. An adhesive similar to the adhesive used to bond the fabric structure 16 to the first polymer coating 15 described above may be used here.
[0070] Typical coatings for the first or second polymer coatings 15 and 19 have a thickness of about 75 microns and an area weight of about 90 gsm. The coatings should have a vertical flame retardancy rating in accordance with UL 94V-0 and be able to withstand exposure from -40 to +60 degrees Celsius without compromising basic mechanical and visual properties (such as flexibility, color, transparency, etc.).
[0071] Practicality
[0072] The composite sheet 11a or 11b described herein has useful fire resistant properties and is suitable as a curtain wall material for cargo containers, particularly containers used in aircraft. Aircraft cargo containers are often referred to as unitary load devices (ULDs). In a preferred embodiment, when assembled into a container frame, the composite sheet 11a or 11b is positioned so that the fabric structure 18 of the textile component 12a or the fabric structure 17 of the textile component 12b is positioned to face the fire threat from the cargo, such as Figure 1 and Figure 2 The fire threat direction is shown in Figure 1 and 2 The composite sheet 11a or 11b complies with the test method described below.
[0073] The term "innermost" used in the present disclosure refers to the portion of the composite sheet facing the cargo when the composite sheet 11a or 11b is assembled into a cargo container. The term "outermost" used in the present disclosure refers to the portion of the composite sheet farthest from the cargo when the composite sheet 11a or 11b is assembled into a cargo container.
[0074] Although the preferred orientation of the composite sheet 11a or 11b is that the fabric structure 18 of the textile component 12a or the fabric structure 17 of the textile component 12b is positioned to face the cargo fire threat, i.e., to contain a fire inside a fire-resistant air cargo container, the composite sheet 11a or 11b will also be able to provide useful fire resistance properties when the opposite sides of the composite sheets 11a and 11b are exposed to a fire outside the cargo container.
[0075] Test Method
[0076] Flame penetration is measured in accordance with 14 CFR 25.855 Appendix F Part III - Test Method to Determine Flame Penetration Resistance of Cargo Compartment Liner (ceiling position). This is referred to as "Test Method 1" in the examples.
[0077] The composite sheet was subjected to a flame test that replicated the temperature and air mass flux test conditions of Test Method FAA FAR 25.856(b) Appendix F, Part VII. The slightly lower heat flux was compensated by a higher air mass flux to replicate the required thermomechanical stress levels imposed on the flame retardant composite sheet during the burn-through test. This is referred to as "Test Method 2" in the Examples.
[0078] The wash-dry cycle consisted of a 4 lb. load with each warm water wash cycle having a duration of 40 minutes. The detergent was 66 g of 1993 AATCC Standard Reference Detergent. Each drying cycle lasted 40 minutes and the drying medium was forced cold air.
[0079] Examples
[0080] The following examples are given to illustrate exemplary embodiments of the present invention and should not be construed as limiting the present invention in any way. Unless otherwise indicated, all parts and percentages are by weight. Examples prepared according to one or more processes described herein are indicated by numerical values. Control examples or comparative examples are indicated by letters.
[0081] In Examples 1-17, once three textile structures 16, 17, and 18 of textile component 12a or 12b are assembled together, textile component 12a or 12b is needlepunched.
[0082] Example 1
[0083] The fabric structure 16 of the textile component 12a is composed of 1500 denier A plain weave para-aramid fabric woven with K29 yarn. This aramid fabric has 26 ends per inch in both the warp and weft. The fabric structure 17 of the textile component 12a is a nonwoven fabric from TexTech Industries of North Monmouth, ME. This nonwoven fabric has a nominal weight of 102 gsm and contains 50 weight percent pre-oxidized polyacrylonitrile fiber type ZOLTEK TM OX and 50 weight percent Beloctex TM Silica fiber. The textile structure 18 of the textile component 12a is a 190 gsm plain weave E-glass fabric (ECG). There is no first or second polymer coating 15 or 19 in this example. The textile component 12a is as shown in FIG. Figure 1 The textile component 12a was subjected to and passed Test Method 1. In this test, the textile structure 18 faced the flame.
[0084] Example 2
[0085] This example was prepared as in Example 1, except that fabric structure 18 of textile component 12a was a 305 gsm 8-beam satin weave style 7781 E-glass fabric. Textile component 12a passed Test Method 1. In this test, fabric structure 18 faced the flame.
[0086] Example 3
[0087] This example was prepared as in Example 1, except that fabric structure 18 of textile component 12a was a 305 gsm 8-beam satin weave style 6781 S-glass fabric. Textile component 12a passed Test Method 1. In this test, fabric structure 18 faced the flame.
[0088] Example 4
[0089] This example was prepared as in Example 1, except that fabric structure 18 of textile component 12a was a 195 gsm 8-beam satin weave style E-glass fabric. In this test, fabric structure 18 faced the flame. Textile component 12a passed Test Method 1. Examples 2, 3, and 4 exhibited better structural integrity than Example 1 after flame exposure.
[0090] A further observation between Examples 1, 2, 3, and 4 is that the fabric structures 16 of the textile components 12a from the test specimens of Examples 1 and 4 exhibited a greater tendency to crack during flame exposure than those of Examples 2 and 3.
[0091] For all four Examples 1 to 4, after flame exposure, the glass fabric structure 18 exhibited The tendency of the fabric structure 16 to detach or peel.
[0092] Example 5
[0093] The textile component 12a of Example 1 was treated with a phenolic resin from Georgia Pacific Chemicals LLC, Atlanta, GA. 445D05 Impregnated so that the resin content is 7% of the combined weight of resin plus fibers in textile component 12a. The resin is cured to form a rigid sheet. Textile component 12a passes Test Method 2. In this test, fabric structure 18 faces the flame.
[0094] Example 6
[0095] This example was prepared in a similar manner to Example 5, except that the resin content was 40% of the combined weight of the resin plus fibers in textile component 12a. The resin was cured to form a rigid sheet. Textile component 12a passed Test Method 2. In this test, fabric structure 18 faced the flame.
[0096] Example 7
[0097] This example was prepared in the manner of Example 1. Textile component 12a passed Test Method 2 before and after being subjected to five wash-dry cycles. In this test, textile structure 18 faced the flame.
[0098] Example 8
[0099] Textile component 12b such as Figure 2The textile structure 16 of the textile component 12b is a 230 gsm plain weave woven from 1500 denier yarns. Fabric having a pick count of 17 yarns / inch in both the warp and weft. Fabric structure 17 of textile component 12b was a nonwoven fabric as used in Example 1. Fabric structure 18 of textile component 12b was a 195 gsm woven 8-beam satin E-glass fabric.
[0100] In this example, there is no first or second polymer coating 15 and 19. The textile component 12b is coated with 445D05 The phenolic resin is impregnated such that the resin content is 24.4 weight percent of the combined weight of the resin plus fibers in textile component 12b. The resin is cured to form a rigid sheet.
[0101] Textile component 12b was subjected to Test Method 2 and passed it.
[0102] Two samples of textile component 12b were subjected to a wash-dry cycle according to Example 7, and two samples were not subjected to a wash-dry cycle to serve as controls. There were no significant performance differences between the washed and unwashed samples when subjected to flame exposure according to Test Method 2. There were also no significant differences in appearance or signs of physical degradation between the four samples.
[0103] In all flame tests of this example, the fabric structure 17 faced the flame.
[0104] Example 9
[0105] This example was prepared in the manner of Example 8, except that textile structure 17 had an area weight of 170 gsm and the resin content was 26.6 weight percent of the combined weight of resin plus fibers in textile component 12b. The resin was cured to form a rigid sheet.
[0106] Textile component 12b was subjected to, and passed, Test Method 2. In this test, textile structure 17 faced the flame.
[0107] Likewise, there were no significant performance differences between the washed and unwashed samples when subjected to Test Method 2. Additionally, there were no significant differences in appearance or signs of physical degradation between the four samples.
[0108] However, the samples from Example 8 exhibited a greater tendency to crack after flame exposure than the samples from Example 9. It was also observed that the test samples subjected to the wash-dry cycle had less smoke and off-gassing during the flame test than the unwashed test samples. A further observation between Examples 8 and 9 was that after flame exposure, the test samples from Example 9 had better residual cohesive integrity than the test samples from Example 8, i.e., the glass fabric structure 18 in Example 8 was less resistant to cracking than the unwashed test samples. The fabric structure 16 peeled off, unlike Example 9 where this did not occur.
[0109] Example 10
[0110] This example was prepared as in Example 9, except that the fabric structure 18 of the textile component 12b was a 190 gsm plain weave E-glass fabric (ECG). In addition, the textile component 12b was not impregnated with resin nor subjected to a wash cycle.
[0111] Textile component 12b was subjected to, and passed, Test Method 1. In this test, textile structure 17 faced the flame.
[0112] Example 11
[0113] This example was prepared as in Example 10, except that fabric structure 18 of textile component 12b was a 305 gsm 8-beam satin weave style 7781 E-glass fabric.
[0114] Textile component 12b was subjected to, and passed, Test Method 1. In this test, textile structure 17 faced the flame.
[0115] There were no significant performance differences between Examples 10 and 11, nor were there any noticeable differences in appearance or levels of physical degradation between the two samples during and after flame exposure.
[0116] Examples 10 and 11 exhibited similar structural integrity after flame exposure as Examples 3 and 4, but the glass fabric structure 18 did not show any signs of cracking after flame exposure. The tendency of the fabric structure 16 to detach or peel off.
[0117] Example 12
[0118] This example was prepared according to Example 10. Textile component 12b passed Test Method 2 before and after being subjected to five wash-dry cycles. In this test, fabric structure 17 faced the flame.
[0119] Example 13
[0120] This example was prepared according to Example 11. Textile component 12b passed Test Method 2 before and after being subjected to five wash-dry cycles.
[0121] There were no significant performance differences between washed and unwashed Examples 12 and 13 when subjected to Test Method 2. Additionally, there were no significant differences in appearance or signs of physical degradation between the four samples during and after flame exposure. In this test, fabric structure 17 faced the flame.
[0122] Examples 12 and 13 exhibited similar structural integrity after flame exposure, with the glass fabric structure 18 not deforming from the glass fabric structure after flame exposure. The tendency of the fabric structure 16 to detach or peel off.
[0123] Example 14
[0124] This example was prepared as in Example 10, except that an opaque 0.075 mm (3 mil) cast polyurethane film was thermally bonded to both first surface 13b and second surface 14b of textile component 12b, thereby providing first polymer coating 15 and second polymer coating 19, respectively.
[0125] This example was subjected to and passed Test Method 1. In this test, the second polymer coating 19 is exposed to a flame with the fabric structure 17 immediately adjacent to the polymer coating 19.
[0126] Example 15
[0127] This example was prepared as in Example 14, except that textile component 12b was treated with phenolic resin. 445D05 The resin is impregnated so that the resin content is 24.5% of the combined weight of the resin plus fibers in the textile component 12b. The resin is cured. An opaque 0.075 mm (3 mil) cast polyurethane film is then thermally bonded to both the first surface 13b and the second surface 14b of the textile component 12b, thereby providing polymer coating 15 and polymer coating 19, respectively.
[0128] The example was subjected to and passed Test Method 2. In this test, the second polymer coating 19 was exposed to a flame with the fabric structure 17 immediately adjacent to the polymer coating 19.
[0129] Example 16
[0130] This example was prepared as in Example 10 except that a white opaque 0.025 mm (1 mil) polymer from DuPont was used. Film grade TWHB10E3 was adhesively bonded to both first surface 13b and second surface 14b of textile component 12b, thereby providing polymer coating 15 and polymer coating 19, respectively. The adhesive used was GH 140FR TP-PU type polyurethane adhesive film from Pioneer Marketing LLC, which contains up to 30 weight percent flame retardant ingredients. The amount of adhesive applied was 34 gsm (1.0 oz / yd 2 ).
[0131] This example was subjected to and passed Test Method 1. In this test, the side of the sample exposed to the flame was the polymer coating 19 with the fabric structure 17 immediately adjacent to the polymer coating 19.
[0132] Example 17
[0133] This example was prepared according to Example 16 except that phenolic resin was used. 445D05 The textile component 12b was impregnated so that the resin content was 24.5% of the combined weight of the resin plus fibers in the textile component 12b. The resin was cured. A white opaque 0.025 mm (1 mil) polymer Film grade TWHB10E3 was adhesively bonded to both first surface 13b and second surface 14b of textile component 12b, thereby providing polymer coating 15 and polymer coating 19, respectively. GH 140FR TP-PU type polyurethane adhesive film containing up to 30 weight percent of flame retardant components was used as an adhesive to bond first polymer coating 15 and second polymer coating 19 to their respective textile structures. The amount of adhesive applied was 34 gsm (1.0 oz / yd 2 .
[0134] This example was subjected to and passed Test Method 2. In this test, the second polymer layer 19 was the side exposed to the flame, with the textile structure 17 immediately adjacent to the polymer coating 19.
[0135] Comparative Example A
[0136] Comparative Example A was prepared as in Example 1, except that fabric structure 17 was omitted. Fabric structures 16 and 18 were not mechanically entangled by needling. This example failed Test Method 1, thus demonstrating the benefit provided by fabric structure 17 in providing enhanced flame retardant properties. In this example, fabric structure 18 faced the flame.
[0137] Comparative Example B
[0138] This comparative example was prepared as in Example 9, except that fabric structure 18 (glass fabric) was omitted in textile component 12b. Both fabrics of textile component 12b were subjected to needle punching. Additionally, textile component 12b was not impregnated with resin, and the assembled textile component 12b was not subjected to a wash cycle. This example failed Test Method 1. In this example, fabric structure 17 faced the flame.
Claims
1. A composite sheet comprising a textile component having a first surface and a second surface and a first polymer coating on the first surface of the textile component, wherein the textile component further comprises a first structure of a woven fabric of at least one continuous filament yarn, said fabric having an area weight of from about 70 to about 508 gsm, a second structure of a nonwoven fabric comprising a blend of discontinuous fibers of oxidized polyacrylonitrile fibers and silica fibers, wherein the oxidized polyacrylonitrile fibers are present in an amount of about 30 to about 70 weight percent of the combined weight of the oxidized polyacrylonitrile fibers and silica fibers, and A third construction of a woven fabric of at least one continuous filament yarn, the fabric having an area weight of about 70 to about 508 gsm.
2. The composite sheet of claim 1, further comprising a second polymer coating on the second surface of the textile component.
3. The textile component of claim 1, wherein: The filaments of the at least one woven fabric of the first structure are aramid, aramid copolyamide, glass, carbon, or aliphatic polyamide.
4. The textile component of claim 1, wherein: The filaments of the at least one woven fabric of the third structure are glass, aramid, aramid copolyamide, carbon, or aliphatic polyamide.
5. The composite sheet according to claim 1, wherein: At least one of the first, second, or third structures is impregnated with a matrix resin such that the resin is present in an amount from about 5 to about 45 weight percent of the combined weight of the resin and fibers in the at least one of the first, second, or third structures.
6. The composite sheet according to claim 1, wherein: The first polymer coating 15 is polyurethane, silicone rubber, polyvinyl chloride, or a blend thereof.
7. The composite sheet according to claim 1, wherein: The second structure is attached to the first structure or the third structure or both the first structure and the third structure by attachment means.
8. The composite sheet according to claim 1, wherein: The third structure is attached to the first structure or the second structure or to both the first structure and the second structure by attachment means.
9. The composite sheet according to claim 2, wherein: The second polymer coating 19 is polyurethane, silicone rubber, polyvinyl chloride, ethylene acid copolymer, or a blend thereof.
10. The textile component of claim 3, wherein: The aramid filaments are para-aramid.
11. The composite sheet according to claim 5, wherein: The matrix resin is a phenolic resin, a flame retardant epoxy resin, a flame retardant polyurethane, or a bio-based resin.
12. The composite sheet according to claim 7, wherein: The attachment means is by bonding, sewing, fiber entanglement, or a combination thereof.
13. The composite sheet according to claim 8, wherein: The attachment means is bonding, sewing, fiber entanglement, or a combination thereof.
14. A cargo container comprising the composite sheet according to claim 1.
Citation Information
Patent Citations
Composite sheet and cargo container comprising same
US10300677B2
Composite sheet and cargo container comprising same
US10457013B2
Aramid copolymer yarn having low residual sulfur
US20140357834A1
Cutting machine
US2045586A
Wholly aromatic polyamides
US3094511A